Characterization and antibacterial activity of nanostructured ZnO thin films synthesized through a hydrothermal method - Nuengruethai Ekthammathat (2018)
Nanostructured ZnO films have been successfully synthesized on Zn substrates by a simple hydrothermal method at 120°C in 24h. The morphologies of the products were controlled by the following alkaline precursor solutions: NaOH, LiOH and NH4OH, which played a role in the crystallization process by generating rod-like, pencil-like and star-like particles, respectively. The phase and crystallinity of the nanostructured films were characterized by X-ray diffraction and selected area electron diffraction, the vibrational modes were determined by Fourier transform infrared spectrometry and Raman spectroscopy, and their morphologies were visualized by scanning electron microscopy and transmission electron microscopy. The photoluminescence of the products exhibited a strong, green-yellow band emission at 540nm. By using the inhibition zone method, the as-synthesized ZnO nanostructures were observed to inhibit bacterial activity. © 2014 Elsevier B.V.